Pyridine derivatives as corrosion inhibitors for N80 steel in 15% HCl: Electrochemical, surface and quantum chemical studies - Ansari K.R.; Quraishi M.A.; Singh A. (My University, 2025)
The present paper deals with the adsorption and inhibitory effects of the pyridine derivatives, namely 2-amino-6-(2,4-dihydroxyphenyl)-4-(4-methoxyphenyl)nicotinonitrile (ADP) and 2-amino-4-(4-methoxyphenyl)-6-phenylnicotinonitrile (AMP) on N80 steel corrosion in 15% HCl. Among the studied compounds, ADP showed the inhibition efficiency of 90.24% at 200 mg/L. The corrosion study was performed by gravimetric, electrochemical impedance spectroscopy (EIS), Tafel polarization, scanning electron microscopy (SEM), scanning electrochemical microscopy (SECM) and energy-dispersive X-ray spectroscopy (EDX) techniques. The Langmuir isotherm model showed the best fit. The quantum chemical study was used to support the experimental results. 2015 Elsevier Ltd. All rights reserved.